Evaluation of the effect of biochar-based organic fertilizer on the growth performance of fennel and cumin plants for three years. Issue 1 (31st December 2022) - Ghani Achakzai, Abdul; Buriro, Abdul Hanan; Gul, Shamim; Ziad, Tariq; Bano, Amna; Ghori, Sadaf Aslam; Ponya, Zsolt; Ismail, Tariq
ABSTRACT: This three years field study examined the influence of application rates of manure from sheep and goat (S/G) and their mixture with wood-based or farm yard manure-based biochars (FYMB) on growth performance of Foeniculum vulgare (fennel) and Cuminum cyminum (cumin). The fertilizer amendment rates were 1.66, 3.32 and 6.64 t ha −1, which were applied for three consecutive years in field. The nitrogen (N) and phosphorus (P), nitrogen use efficiency (NUE) and phosphorus use efficiency (PUE) in seeds and stover of test crops were analyzed for third year cropping only. Results demonstrated that in general, fertilizers did not influence yield of first and second year crops. The significant (P ≤ 0.05) positive influences of organic fertilizers were observed for third year crops and were of higher magnitude for C. cyminum than F. vulgare (126–306.6% increase for C. cyminum and 24.5–48.4% increase for F. vulgare than control). As compared to S/G applied at 6.64 t ha −1 rate, its co-amendment with wood-derived biochar at all application rates significantly reduced P in seeds; whereas, its co-amendment with both biochar types and at all application rates significantly reduced P in the stover of F. vulgare (Table 3; P ≤ 0.05). For the crop C. cyminum, there was no difference between treatments for the concentration of P in stover. The phosphorus use efficiency (PUE) of stover of F. vulgare was significantly improved by 80–108% and by 60–79% in response to the application of S/G and its co-amendment with FYMB respectively than control. The PUE of seeds of F. vulgare was increased by 100% than control in response to the co-amendment of manure with wood-derived biochar at high application rate (P ≤ 0.05). More profound significant improvement in PUE was observed for third year crop of C. cyminum, as most of the treatments improved PUE of seeds by171 – 561% and stover by 196–294% than control with no significant differences between fertilizer treatments. Results show no relationship between fertilizer application rates and life history trait of crops in space and time, since there was non-consistent and in general non-significant differences between fertilizer treatments for both crops.